Coupled influence of content, gradation and shape characteristics of silts on static liquefaction of loose silty sands. Issue 101 (October 2017) - Monkul, Mehmet Murat; Etminan, Ehsan; Şenol, Aykut
Abstract: Static liquefaction is a challenging problem of geotechnical engineering as its consequences are generally catastrophic when they occur on site. Previous laboratory studies focused on various factors that could influence the static liquefaction potential of silty sands. Most popular of those investigated factors are stress conditions, deposition method and fines content. The purpose of the present study is to investigate the other possible factors, of which very little is known, mainly focusing on the silt characteristics including grain size distribution, relative size, and shape effects of the silt grain matrix within the sand. Undrained monotonic triaxial compression tests were conducted on thirty sands with varying fines contents, which were prepared by mixing three base sands (Sile Sands 20/30, 50/55, 80/100) with same geologic origin but with different gradations and three different non-plastic silts (IZ, SI and TT silts) with different gradations and shape characteristics. The experimental results revealed that each of the mentioned factors had their own influence on static liquefaction behavior of sands. The static liquefaction potential of all the three sands in this study was observed to increase with decreasing coefficient of uniformities of the silt grain matrix (CUsilt ) in sands. For a particular base sand, static liquefaction potential was observed to increase with decreasing mean grain diameter ratio (D50-sand /d50-silt ) due to change of silt gradation. However, shape characteristics of the silt grains are also found to be another important factor, in certain cases observed to have a greater influence than mean grain diameter ratio criterion. As an example, it was shown that at the same FC, base sand, depositional energy and consolidation stress, angular nature of TT silt potentially caused more meta-stable contacts (weaker grain contacts that promote excess pore pressure generation during shearing) within the specimens than sub-rounded SI silt, which caused specimens with TT silt to be more liquefiable than their counterparts with SI silt. Moreover, it was found that there is a coupled relationship between the fines content and investigated silt characteristics (gradation, mean size, shape effects) on the static liquefaction behavior of sands. The unexpected trend regarding the last finding is that the mentioned influence of silt characteristics (i.e. gradation, size and shape) on static liquefaction of sands becomes more considerable with decreasing fines content at loose states. Highlights: Static liquefaction potential of Sile Sands has systematically increased with FC. Both CUsilt and D50-sand /d50-silt was observed to influence the liquefaction behavior. Shape effects of the silts was shown to influence the liquefaction behavior as well. There is a coupled relationship btw FC and influence of various silt characteristics.